Получение биотоплив гидрокрекингом растительного и композиционного сырья - Григораш М. С. Михаил Степанович; Ваганов Р. А. Роман Александрович; Ивашкина Е. Н. Елена Николаевна; Смирнова Н. А. Наталья Александровна; Чекменёва Д. В. Дарья Вячеславовна (2024, 2024)
Заглавие с экрана.